Coplanar waveguide fed 9-point star shape monopole antennas for worldwide interoperability for microwave access and wireless local area network applications - Tapan Mandal (The Journal of Engineering, 2014)
In this Letter, a coplanar waveguide fed monopole antenna with a band stop characteristic is proposed for worldwide interoperability for microwave access (WiMAX) and wireless local area network (WLAN) applications. The antenna has a small size of 30 × 45 mm^2. The antenna consists of a 9-point star radiating patch. The band rejection characteristic is realised by introducing a pair of L-shaped slots in the ground plane. The prototype and proposed antennas have been constructed and experimentally studied. The measured return loss shows a reasonable agreement with the simulated one. Impedance and radiation characteristics of the antenna are studied. It is found that the results are suitable for 3.05–3.84 GHz WiMAX and 5.15–5.825 GHz WLAN applications. The antenna exhibits omni-directional radiation pattern and appreciable gain across the operating bands. It is suitable for portable wireless communication systems.